PENGELOLAAN SEKOLAH BERBASIS RELIGI STUDI SITUS MADRASAH ALIYYAH FUTUHIYYAH - 1 MRANGGEN DEMAK - ROHMAN, ARIP (2011)
This study objective to describe the Relegion-Based School Management of Study Site in Madrasah Aliyyah Futuhiyyah -1 Mranggen Demak. This research is a qualitative research in etnogarfi design. The experiment was conducted in MA.Futujiyyah - 1 Mranggen Demak. Resource persons in research is the principal, assistant principal, teachers, and staff offices. Data collection methods using depth interviews, observation, and documentation. Data analysis using analysis are arranged in the site, with interactive models that start from (1) data reduction, (2) presentation of data, and (3) conclusion. Validity of data include the level of confidence (credibility), keteralihan (transferability), dependence (dependabibility), and certainty (confirmability). The results of the research showed that: (1). Characteristics of School- Based Management of Religion in Madrasah Aliyyah Futuhiyyah - 1 Mranggen Demak using the concept of School-Based Management or Madrasah Based Management which in this case to achieve the improvement of the quality of school education because of the MBS to provide authority and broad responsibilities for schools based on professionalism to organize school organization, seek and develop and utilize the available educational resources, and improve school performance. (2) The Working Relationships Between Components of School-Based Support In Managing Religion in Madrasah Aliyyah Futuhiyyah - 1 Mranggen. The working relationship between school administrators or with society support each other so that the process of attainment of the objectives as stated in the vision the school has run smoothly and can be performed independently by the Madrasah by involving communities in decision- making . So madrassa to develop a vision that has existed in accordance with the circumstances or conditions in the area. (3) Activity-Based In Religion in Madrasah Schools Aliyyah Futuhiyyah - 1 Mranggen activity contained in the religious-based schools in this regard is the madrassa Aliyyah Futuhiyyah - 1 Mranggen almost equal to other formal schools or madrassas level Madrasah Aliyyah other but this will have a unique value or unique point of combining the formal school curriculum with a curriculum that is in boarding school.